Digestibilidade aparente de ingredientes pela tilápia-do-Nilo em tanques rede - Sato, Leonardo Seiji [UNESP] (2016)
The aim of this study was to evaluate the apparent digestibility of ingredients for Nile tilapia in intensive production system, in two fish sizes, growing and finishing. The experiment was conducted in fish farming Fernandes, Palmital, SP, canoas II reservoir, Paranapanema River. Nile tilapia (Oreochromis niloticus) 60-500 g, were stocked in 24 tanks 1.0 m3 net cage. Apparent digestibility coefficient was determined by an indirect method, using 0.1 % chromic oxide (Cr2O3) as marker. The experimental design was completely randomized in a factorial arrangement (3x2), three treatments (corn, wheat meddlings and rice bran or poultry meal, meat and bone meal and soybean meal) and two fish sizes (50-500g) with six replicates each. The apparent digestibility coefficients (ADC) of dry matter, crude protein, gross energy, lipids, and the apparent availability of phosphorus, magnesium, zinc, and manganese were determined. Among the energetic ingredients corn showed the highest values, followed by rice bran and wheat meddlings. Among the protein ingredients poutry meal showed the highest values, than soybean meal and meat and bone meal. This study demonstrated that the apparent digestibility coefficient can be influenced by fish size, since corn, rice bran and poultry meal, showed the highest digestibility coefficients for 500 g fish, however wheat meddlings showed the highest coefficient for 50 g fish